Britain and the abdication of Reza Shah. Issue 2 (3rd March 2016) - Bakhash, Shaul
ABSTRACT: On the eve of the Anglo-Soviet invasion of Iran in the Second World War, Sir Reader Bullard, the British minister in Tehran, urged on his government the desirability of removing the Iranian ruler, Reza Shah, from office. Association with the 'universally detested' shah, whom he described as a 'greedy ignorant savage', was detrimental to Britain's interests and its war effort. In the weeks that followed the Anglo-Soviet occupation of Iran, Bullard continued to press for and to shape the ultimate British decision to force Reza Shah to abdicate and go into exile. Yet, this was not always Bullard's view of Britain's relationship with the Iranian ruler. When he presented his credentials 20 months earlier, Bullard described it as his 'urgent duty' to win Reza Shah's favour. Nor did Bullard's insistence that Britain depose the Shah initially find favour with the Foreign Secretary, Anthony Eden, his Middle East staff at the Foreign Office, or with Churchill. This article traces the evolution of Bullard's own view of Reza Shah and the developments that led the Foreign Office, initially eager to win Reza Shah's favour and even ready to offer Reza Shah a 'substantial bribe' for his cooperation, to take steps to topple Reza Shah from the throne.